Risk of hepatitis C virus infection among health care workers in their occupational practice - Sierpińska, Lidia (Journal of Education, Health and Sport, 2017)
Introduction. Hepatitis C virus infection is a serious clinical, epidemiological, and social problem in Poland and worldwide. This type of infection is often registered as: hospital-acquired infection, infection among health care workers, infection of a newborn transmitted via vertical route. Health care professionals are occupationally exposed to HCV. Objective. Presentation of the problem of risk of acquiring HCV infection among medical staff employed in health care facilities. Material and methods. Epidemiological data were analyzed concerning infections with hepatitis C virus from the aspect of exposure of medical staff employed in health care facilities, based on the published results of scientific studies and statistical data. Results. HCV infection among medical professionals employed in health care facilities is a multi-aspect problem, which should be considered as the problem of: hospital-acquired infections, occupational infections, and vertically transmitted infections. Conclusions. Hepatitis C virus infection is a serious clinical, epidemiological, and social problem in Poland, and concerns approximately 1.9% of the population. This is one of the leading causes of hospital-acquired infections – approximately 33%. Health care workers are occupationally exposed to HCV infection – in Poland this risk is from 0.80-1.42%. Care of a pregnant woman infected with HCV and care of a newborn with vertically transmitted infection creates risk for medical staff. Considering high occupational risk of HCV infection among health care workers it is necessary to carry out a wide range of non-specific prophylaxis, and also observe procedures for prevention of occupational exposures.